Dynamic stall induced by blade vortex interaction in helicopter descending flight - Gibertine, G.; Colli, A.; Zanotti, A. (My University, 2019)
In recent years studies have shown how blade-vortex interaction (BVI) can cause the onset of dynamic stall on helicopter rotors. In order to investigate this phenomenon wind tunnel tests were performed on a rotor model in descent flight conditions. The anaylsis of the rotor global performances indicated a defect of thrust for a particular value of collective pitch angle that can be explained as the occurrence of dynamic stall induced by a perpendicular vortex interaction. This conclusion is supported by evidence from both flapping angle measurements and by the results of numerical simulations performed using a code based on blade-element coupled with a vortex-particle wake model.